STRATEGI PEMENANGAN PASANGAN ADE UU SUKAESIH-DARMADJI PRAWIRASETIA (ASIH-KATADJI) DALAM PEMILU WALI KOTA BANJAR PERIODE 2013-2018 - WIDIASTUTI, WIWI (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Research that was headlined Strategy Winning Couples Ade Uu Sukaesih-Darmadji (Asih-Katadji) in Elections the Mayor of Banjar a period of 2013-2018 is done in the city of Banjar of West Java. The study is done because researchers were interested in strategies couples asih-katdji in winning the election the Mayor of Banjar. Reason researchers uninterested because of Ade Uu sukaesih is the wife of the Mayor of Banjar who was served. The study is done by using the method research qualitative. The informer done with the methods purposive of sampling by choosing the informant who know that strategy in winning couples asih-katadji in elections the mayor of banjar. The result of field research proves that couples asih-katadji do marketing strategy push by means of direct contact through various events like the general meeting of party, entertainment stage, declaration partai the coalition, and the rally. Marketing strategy other is pass through the influence of a figure or a particular group as a team of success. In strategy pass marketing is done by using services coalition party, volunteers Restu, volunteers asih and volunteers adji. Besides two strategies push marketing, and pass used also strategy pull marketing by using services media including free media and paid media. Research is unique, because there are other factors that supports a pair of asih-katadji. Factors it is the length of the campaign, the role of Guardian City Banjar who performs style blusukan at eighteen location every day, to remind the people of the merits of a trustee city that is the husband of Ade Uu sukaesih. In addition, the mayor of Banjar is also involved in any process from the beginning of nominating to be chosen.